2020
DOI: 10.1038/s41396-020-0645-z
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variant analysis reveals poor correlations in microbial taxonomic abundance between humans and mice after gnotobiotic transfer

Abstract: Transplanting human gut microbiotas into germ-free (GF) mice is a popular approach to disentangle cause-and-effect relationships between enteric microbes and disease. Algorithm development has enabled sequence variant (SV) identification from 16S rRNA gene sequence data. SV analyses can identify which donor taxa colonize recipient GF mice, and how SV abundance in humans is replicated in these mice. Fecal microbiotas from 8 human subjects were used to generate 77 slurries, which were transplanted into 153 GF mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 37 publications
5
30
0
Order By: Relevance
“…Fecal materials, the excreted residue of the digestive tract, fail to capture the overall variation in bacterial colonization along the entire GI-tract because of the absence of the SI microbiota. In many previous studies using humanized mice, microbes successfully colonizing the recipient intestine also primarily originated from the largeintestinal microbiome of donors, such as Lachnospiraceae, Prevotellaceae, and Ruminococcaceae, with few smallintestinal microbes colonized [72][73][74][75]. These outcomes are in line with our study and indicate the missing effects of the small-intestinal microbiota of donors in these FMT studies.…”
Section: Niche-specific Colonization Of Exogenous Microbiota Across Dsupporting
confidence: 89%
“…Fecal materials, the excreted residue of the digestive tract, fail to capture the overall variation in bacterial colonization along the entire GI-tract because of the absence of the SI microbiota. In many previous studies using humanized mice, microbes successfully colonizing the recipient intestine also primarily originated from the largeintestinal microbiome of donors, such as Lachnospiraceae, Prevotellaceae, and Ruminococcaceae, with few smallintestinal microbes colonized [72][73][74][75]. These outcomes are in line with our study and indicate the missing effects of the small-intestinal microbiota of donors in these FMT studies.…”
Section: Niche-specific Colonization Of Exogenous Microbiota Across Dsupporting
confidence: 89%
“…However, antibiotic doses used in mice experiments create an almost germ-free environment after treatment, which is unlikely to apply to the human gut with clinical use of antibiotics. Furthermore, the mice gut microbiome and human gut microbiome differ considerably [41][42][43]. For example, many Firmicutes spp., which represent major colonizers of the human gut, cannot efficiently colonize the murine gut.…”
Section: Discussionmentioning
confidence: 99%
“…Although no PCL gyrB sequence was detected in mouse gut bacterial gene catalog, which was generated from common laboratory mice (non-humanized) (60), a recent study verified the reliable transmission of Prevotellaceae from human feces to germfree mice (61). Our investigation on the PCL members in captive mammals suggested that these bacteria recently originated from sympatric human hosts and potentially experienced niche selection, e.g., g8 of P. copri in bovines and pigs.…”
Section: Non-strict Biogeography and Host For Pcl Members Suggest Limmentioning
confidence: 70%